2023
DOI: 10.1136/thorax-2022-219268
|View full text |Cite
|
Sign up to set email alerts
|

Effect of obesity on airway and systemic inflammation in adults with asthma: a systematic review and meta-analysis

Abstract: BackgroundObesity is associated with more severe asthma, however, the mechanisms responsible are poorly understood. Obesity is also associated with low-grade systemic inflammation; it is possible that this inflammation extends to the airways of adults with asthma, contributing to worse asthma outcomes. Accordingly, the aim of this review was to examine whether obesity is associated with increased airway and systemic inflammation and adipokines, in adults with asthma.MethodsMedline, Embase, CINAHL, Scopus and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…Numerous studies provide evidence indicating that obesity is linked to a significant increase in various inflammatory markers, potentially intensifying the inflammatory processes in individuals with asthma. Asthmatic individuals who are obese demonstrate notably elevated levels of inflammatory markers, including blood and sputum neutrophils (176,187), bronchial sputum eosinophil count (187), sputum IL-5 (187), blood IL-6 (187,188), CRP (187,189,190), TNF-α (188), and leptin (187,188,(190)(191)(192), in comparison to their non-obese counterparts with asthma. Additionally, obese asthma patients often exhibit a distinct phenotype characterized by neutrophilic inflammation.…”
Section: Asthma and Obesitymentioning
confidence: 99%
“…Numerous studies provide evidence indicating that obesity is linked to a significant increase in various inflammatory markers, potentially intensifying the inflammatory processes in individuals with asthma. Asthmatic individuals who are obese demonstrate notably elevated levels of inflammatory markers, including blood and sputum neutrophils (176,187), bronchial sputum eosinophil count (187), sputum IL-5 (187), blood IL-6 (187,188), CRP (187,189,190), TNF-α (188), and leptin (187,188,(190)(191)(192), in comparison to their non-obese counterparts with asthma. Additionally, obese asthma patients often exhibit a distinct phenotype characterized by neutrophilic inflammation.…”
Section: Asthma and Obesitymentioning
confidence: 99%
“…Western lifestyle includes Western dietary patterns with high caloric intake combined with low physical activity, which certainly play a key role in the development of obesity. This disease is related to poorer asthma control and lung function, as well as an increased risk of asthma exacerbations [1].…”
Section: Western Diet As a Risk Factor For Asthmamentioning
confidence: 99%
“…It is known that the causes involve, to a large extent, immunomodulation of the adaptive and specifically the innate immune systems. Moreover, causes seem to be markedly influenced by distinct environmental triggers and genetic interactions that challenge the immune system [1]. With this background, there are many research gaps in the knowledge, despite the fact that asthma is a global health problem affecting about 10-15% of children around the world [2] and more than 15% of school-aged children in Europe [3].…”
Section: Introductionmentioning
confidence: 99%
“…[ 262 ] Studies has shown that obese asthmatics have a different pattern of inflammation when compared to non-obese asthmatics. [ 263 ] Therefore, Obese asthma patients have more symptoms, more frequent and severe exacerbations, reduced response to asthma medications, poor quality of life and more difficult to control asthma. [ 264 ] This could be in part related to reduced lung volumes, lack of fitness, and associated sleep apnea and GERD.…”
Section: Section 8: Asthma In Special Situationsmentioning
confidence: 99%